Using genomic information for management planning of an endangered perennial, Viola uliginosa. Issue 5 (17th February 2020) - Lee, Kyung Min; Ranta, Pertti; Saarikivi, Jarmo; Kutnar, Lado; Vreš, Branko; Dzhus, Maxim; Mutanen, Marko; Kvist, Laura
Abstract: Species occupying habitats subjected to frequent natural and/or anthropogenic changes are a challenge for conservation management. We studied one such species, Viola uliginosa, an endangered perennial wetland species typically inhabiting sporadically flooded meadows alongside rivers/lakes. In order to estimate genomic diversity, population structure, and history, we sampled five sites in Finland, three in Estonia, and one each in Slovenia, Belarus, and Poland using genomic SNP data with double‐digest restriction site‐associated DNA sequencing (ddRAD‐seq). We found monophyletic populations, high levels of inbreeding (mean population F SNP = 0.407–0.945), low effective population sizes ( N e = 0.8–50.9), indications of past demographic expansion, and rare long‐distance dispersal. Our results are important in implementing conservation strategies for V. uliginosa, which should include founding of seed banks, ex situ cultivations, and reintroductions with individuals of proper origin, combined with continuous population monitoring and habitat management. Abstract : We investigated endangered and nonendangered populations of a violet, Viola uliginosa, to estimate genomic diversity, population structure, and history from genomic data. We found monophyletic populations, high levels of inbreeding, and low effective population sizes and indications of past demographic expansion and rare long‐distance dispersal. These are proposed to include the founding of seed banks, ex situ cultivations, and reintroductions with individuals of proper origin, combined with continuous population monitoring and habitat management.